2019
DOI: 10.18203/2394-6040.ijcmph20191826
|View full text |Cite
|
Sign up to set email alerts
|

Study on attitude of household waste management in a rural area of Northern Kerala

Abstract: Background: Proper waste management is a major concern of public health. It is necessary to create positive behavioural changes towards waste management among public in order to control diseases. Objectives were to determine the attitude towards solid and liquid waste management among the households of Cheruthazham Panchayat in Northern Kerala.Methods: A community based cross sectional study was conducted in Cheruthazham Panchayat, under Kalliasseri block, located in Kannur district of Kerala state from June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
4
7
0
Order By: Relevance
“…However, this sorting of solid waste aimed to be used as fertilizer, fuel wood, feeding animals, and salable to "Quraleos and liwach". A similar report was done by Kaithery and Karunakaran (2019). This study shows a higher respondent rate compared to the report done in Wolita Sodo Town (Solomon, 2018).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, this sorting of solid waste aimed to be used as fertilizer, fuel wood, feeding animals, and salable to "Quraleos and liwach". A similar report was done by Kaithery and Karunakaran (2019). This study shows a higher respondent rate compared to the report done in Wolita Sodo Town (Solomon, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…But only small proportions of wastes were recycled by informal collectors in unregulated and unsafe ways. Similar reports were done in Northern Kerala and the majority of Ethiopian City (Kaithery and Karunakaran, 2019;Teshome, 2020). Large proportions of the respondents were having the ''knowledge'' on solid waste management practice, but didn't practice properly.…”
Section: Discussionsupporting
confidence: 63%
“…Before the actual conduct, pre-testing was carried out to examine the content validity of the questions asked in the survey (including semi-structured interview). All questions were refined based on the feedback from both experts in the field and laymen and were adapted from studies in past literature [30,[33][34][35][36][37][38][39] to improve their reliability and representativeness to the study. The questionnaire survey was constructed using an online survey administration application, Google Form, and distributed through various online platforms (e.g., Facebook, Instagram, and WhatsApp, popular applications in Malaysia).…”
Section: Data Collection and Samplingmentioning
confidence: 99%
“…This result was lower than studies in Ethiopia (76.9%), 32 Pakistan (95%), 33 and India (93.8%). 34 The disparity could be influenced by cultural differences and the way waste is managed in the towns, sample sizes, data collection methods and study periods. The present study found that 51.4% of participants reported poor WWM practices.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, resident attitudes were correlated with the level of knowledge, as indicated by previous work. 33,34,38 It could be suggested that good knowledge would lead to good attitudes towards waste handling and management measures. 39 Space availability was another factor that significantly associated with attitudes.…”
Section: Discussionmentioning
confidence: 99%